Effect of Maternal BMI on Nonstress Test Parameters, Breastfeeding Success and Postpartum Depression - Sabanci Baransel, Esra; Barut, Sümeyye; Uçar, Tuba (Ataturk Universitesi, 2024)
Objective: This study aimed to determine the effect of maternal BMI on NST parameters, breastfeeding success and postpartum depression. Method: This cross-sectional study was conducted with 427 women between September 2022 and April 2023. Women who gave birth by vaginal or cesarean delivery and agreed to participate in the study were included in the study. The data of the study were collected using the Introductory Information Form, the LATCH Breastfeeding Diagnostic Scale, and the Edinburgh Postpartum Depression Scale (EDSS). Results: In the study, 57.4% of the women were at normal weight according to their pre-pregnancy BMI, 41.9% were at normal weight according to their BMI at birth, and 99.5% of them were overweight or underweight during pregnancy. received was determined. In the NST according to BMI at birth, 92.9% of those with baseline tachycardia were obese, 53.4% of those with a deceleration number of 3 or more were obese, and the difference between the groups was statistically significant. In the study, it was determined that as BMI before pregnancy and at birth increased, the mean breastfeeding score decreased. In the study, it was determined that the success of breastfeeding was low and the risk of postpartum depression was high in those who were obese before pregnancy and at birth (p<.05). Conclusion: As a result, it was determined that high BMI during pregnancy and delivery may cause negative birth outcomes, negatively affect breastfeeding behavior, and increase the risk of postpartum depression. © 2024, Ataturk Universitesi. All rights reserved.
Maternal BKİ’nin Nonstres Test Parametreleri, Emzirme Başarısı ve Doğum Sonu Depresyona Etkisi
Keywords: Body mass index; maternal; nonstress test; postpartum depression; pregnancy